2017
DOI: 10.18805/ag.v38i02.7940
|View full text |Cite
|
Sign up to set email alerts
|

Developments in computer vision system, focusing on its applications in quality inspection of fruits and vegetables-A review

Abstract: Quality inspection of food is a tedious and labor intensive process. Ever-increasing population, losses in handling and processing and the increased expectation of food products of high quality and safety standards has raised the need for accurate, fast and objective quality determination methods. Manual quality inspection is a slow, costly, unreliable process and suffers from poor repeatability. Computer vision provides one alternative for an automated, non-destructive and costeffective technique to accomplis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Many image processing methods are easily affected by different lighting conditions. Therefore, the adjustment of the lighting system significantly affects the quality of the image and plays an important role in the overall efficiency and accuracy of many applications [22]. A well‐adjusted lighting condition can enhance the image quality, thereby improving image analysis and reducing blur and noise in the image.…”
Section: Methodsmentioning
confidence: 99%
“…Many image processing methods are easily affected by different lighting conditions. Therefore, the adjustment of the lighting system significantly affects the quality of the image and plays an important role in the overall efficiency and accuracy of many applications [22]. A well‐adjusted lighting condition can enhance the image quality, thereby improving image analysis and reducing blur and noise in the image.…”
Section: Methodsmentioning
confidence: 99%
“…High costs, tediousness and inconsistency associated with manual sorting and grading have been forcing the post harvest industry to apply automation in these postharvest operations. Chopde et al (2017) identified computer vision technology as an emerging technique in sorting and grading of fruits and vegetables that will improve productivity of industry and will also help to provide better quality produce to consumers. Kavdir and Guyer (2003) exploited the use of high-tech sensors or machine vision for apple grading and making the final grading decision using Fuzzy Logic, a computer based ap-S264 Eco.…”
Section: Application Of Ai In Fruit Gradingmentioning
confidence: 99%
“…Machine vision technology based on visible imaging system has become widely used for bruise detection in fruits over the past few years [79]. However, early changes in bruise area for fruit are difficult to be detected by traditional RGB vision system for part of fruits including cheery [10].…”
Section: Introductionmentioning
confidence: 99%